Remoção de sulfetos em sistemas anaeróbios utilizando efluente nitrificado - Silva, Pedro Ivo Soares e (2020)
Anaerobic treatment is effective in removing a large fraction of organic matter when treating domestic sewage and it is advantageous because it has less sludge production, in addition to low operating and energy costs. In the sulfetogenesis stage, through the action of sulfate-reducing bacteria, the formation of sulfides occurs, this process presents a disadvantage due to the formation of odorous gases, therefore a post-treatment is required to remove the remaining organic matter and nutrients. Therefore, the objective of this study was to evaluate the removal of sulfides in an anaerobic filter with a polyurethane bed, using nitrified effluent from activated sludge as electron acceptors. The experimental system consists of a UASB reactor followed by an anaerobic filter with a polyurethane bed. The study was developed in two experimental phases, in the first one it was used domestic sewage and in the second sanitary sewage. At the entrance of the anaerobic filter, the anaerobic effluent was mixed with the activated sludge effluent in order to maintain nitrate as an electron acceptor in the oxidation of sulfides. Regarding the carbonaceous material in the two phases, total COD removal occurred between 82 and 90%. There was removal of nitrate and sulfides of 71.37% and 96% respectively when compared to the effluent from the UASB reactor. Thus, the integration of nitrogen, carbon and sulfur cycles is relevant in the post-treatment of anaerobic effluents, in this configuration, promoting low treatment costs and allies to obtain an effluent with a lower concentration of nutrients and odorous compounds.